2021
DOI: 10.15212/cvia.2021.0019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Durations of Hospitalized Patients with COVID-19 in Beijing: A Retrospective Cohort Study

Abstract: Objective: To provide information on clinical characteristics and different durations of COVID-19 and to identify thepotential risk factors for longer hospitalization of patients with COVID-19.Methods: In this retrospective study, we enrolled 77 patients (age 52 ± 20 years; 44.2% males) with laboratory confirmedCOVID-19 admitted to Beijing YouAn Hospital between January 21 and February 8, 2020. Epidemiological,clinical, and radiological data on admission were collected; complications and outcomes were followed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 13 publications
1
21
0
8
Order By: Relevance
“…Likewise, a Chinese study represented that bilateral pneumonia in a lung CT scan, a short period from symptoms onset to hospitalization, lymphopenia, and disease severity were the main factors in prolonged LOS (ProLOS). 44 Limitations of this study include the lack of accessibility to the molecular kit at the beginning of the pandemic. Therefore molecular confirmation of COVID-19 was impossible for all included patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, a Chinese study represented that bilateral pneumonia in a lung CT scan, a short period from symptoms onset to hospitalization, lymphopenia, and disease severity were the main factors in prolonged LOS (ProLOS). 44 Limitations of this study include the lack of accessibility to the molecular kit at the beginning of the pandemic. Therefore molecular confirmation of COVID-19 was impossible for all included patients.…”
Section: Resultsmentioning
confidence: 99%
“…29 Chinese research explained that bilateral pneumonia, shorter duration of onset to admission, lymphopenia, and disease severity are regarded as risk factors of prolonged hospitalization of COVID-19. 30 Lymphopenia may occur along with an increased level of cytokine, disease severity, mortality, and impaired immune response. 31 Tan et al 32 showed the inverse relationship between lymphocyte count and disease severity and its prognosis in 92 COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies were conducted between January 2020 and June 2020: 7 in January, 112 in February, 50 in March, 28 in April, 15 in May, and 3 in June. Seventeen preprint studies (Chen et al, 2020a, 2020b; Duan et al, 2020; Fu et al, 2020; Kuang et al, 2020; Li et al, 2020; Liu et al, 2020; Nie et al, 2020; Qi et al, 2020a, 2020b; Qin et al, 2020; Shi et al, 2020; Song et al, 2020; Tao et al, 2020; Wen et al, 2020; Xu et al, 2020; Zhao et al, 2020) were included in the analysis. All the studies included in this meta-analysis were of retrospective design.…”
Section: Resultsmentioning
confidence: 99%
“…[ 2 ] The virus, owing to its high infectivity, spreads quickly and widely, and its numbers are still increasing. [ 3 ]…”
mentioning
confidence: 99%